A REVIEW OF THE LITERATURE: THE USAGE OF DIGITAL GAMIFICATION IN EDUCATION TO IMPROVE MATHEMATICAL PROBLEM-SOLVING SKILLS AND MENTAL HEALTH - Dwi Laksana, Sigit; Dwi Saputro, Anip; Hidayah, Karomatul; Sa'diyatul Wafa, Salamah (Al-Mudarris: Journal Of Education, 2024)
Mathematics is one of the important subjects for students. Mathematics subjects focus more on the ability to remember, memorize, and interpret. it can train students to think logically, analytically, systematically, critically, and creatively in solving problems. The application of gamification in mathematics is an effective strategy. The use of gamification can also support children's mental health, because the use of gamification can reduce stress levels in children. The purpose of this study is to investigate and analyze research articles that explore the main problems in learning mathematics, how the use of gamification can improve math problem solving skills and support mental health, and problems or obstacles in the application of gamification in learning mathematics. Specifically, this literature review also wants to explain the implementation of gamification in mathematics learning to improve problem solving skills and support mental health. This research is a systematic literature review on the use of gamification in mathematics to improve problem solving skills, this review is limited to peer review articles published between 2019 and 2021. One of the ways used to search for related articles, researchers use the POP (Publish or Perish) application. and other relevant sources. This makes it easier for researchers to identify articles, while for sources, researchers take articles from several publishers such as Scopus, IEEE and Google Scholar. The findings of the data analysis show that the use of gamification in mathematics learning has been carried out in various forms and application models, but its implementation is only limited to improving learning abilities. not many researchers have added mental health aspects in the application of gamification, active student involvement will certainly improve students' mental health, so children are not easily stressed. The use of technology-based gamification applications is the main strategy to improve students' problem solving abilities as well as to improve understanding and learning outcomes and support mental health so that the learning experience becomes durable